Efektifitas Penggunaan E-Learning dalam Evaluasi Hasil Belajar di Madrasah Aliyah Negeri 1 Pangandaran - Predi Supriadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to determine the effectiveness of the use of e-learning in evaluating learning outcomes at MAN 1 Pangandaran. This research uses qualitative methods, with the research subjects being the principal, vice principal of curriculum, and teachers. The research was conducted at MAN 1 Pangandaran. Data collection techniques used in this study were observation, interviews, and documentation conducted directly to the field. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed that the use of e-learning in evaluating learning outcomes was quite effective. The benchmark in knowing the effectiveness is through three benchmarks, namely goal achievement, integration and adaptation. In achieving the objectives of the use of e-learning in evaluating learning outcomes at MAN 1 Pangandaran is the implementation of the vision and mission of the Institute. Furthermore, the integration process is also well implemented and can be said to be quite effective both in socialization and communication between the parties involved. Then in Adaptation is also quite good because MAN 1 Pangadaran applies e-learning gradually so that it makes it easier for each party to adapt.